Fatigue analysis of welded joints - Koh, Jackson Wen Qiang (2019)
This report investigated the fatigue growth of a semi-elliptical surface crack in a finite plate and rod using a Failure Assessment Diagram (FAD) approach. The procedure used was based on the British Standard (BS7910) and simulated with the Matlab program. Stress intensity factor solutions from Koterazawa and Minamisaka; Holdbrook and Dover were in comparison with BS7910. Significant findings were concluded from these case studies. Firstly, the plastic collapse parameter, Lr prediction is closer to the real-value if evaluated with limit load method. Secondly, the final stress intensity factor for crack depth is always lower than the crack length direction for both plate and rod. Also, specimen undergoing high stress range will tend to have fatigue failure due to plastic collapse. However, more research needs to be done to cross check the findings, especially for large crack fatigue propagation.